Elevated expression of glycolytic genes as a prominent feature of early-onset preeclampsia: insights from integrative transcriptomic analysis - He, Jie; Yang, Huan; Liu, Zheng; Chen, Miaomiao; Ye, Ying; Tao, Yuelan; Li, Shuhong; Fang, Jie; Xu, Jiacheng; Wu, Xiafei; Qi, Hongbo (Frontiers in Molecular Biosciences, 2023)
Preeclampsia (PE), a notable pregnancy-related disorder, leads to 40,000+ maternal deaths yearly. Recent research shows PE divides into early-onset (EOPE) and late-onset (LOPE) subtypes, each with distinct clinical features and outcomes. This study integrated transcriptomic expression data from a total of 372 placental samples across 8 publicly available databases, and results reveal a complex classification of PE placental samples, wherein EOPE manifests as a highly homogeneous sample group characterized by hypoxia and HIF1A activation. Among the core features is the upregulation of glycolysis-related genes, particularly HK2, in the placenta-an observation corroborated by independent validation data and single-cell data. Building on the pronounced correlation between HK2 and EOPE, we conducted in vitro experiments to assess the potential functional impact of HK2 on trophoblast cells. Additionally, the LOPE samples exhibit strong heterogeneity and lack distinct features, suggesting a complex molecular makeup for this subtype. Unsupervised clustering analysis indicates that LOPE likely comprises at least two distinct subtypes, linked to cell-environment interaction and cytokine and protein modification functionalities. In summary, these findings elucidate potential mechanistic differences between the two PE subtypes, lend support to the hypothesis of classifying PE based on gestational weeks, and emphasize the potential significant role of glycolysis-related genes in EOPE. Preeclampsia (PE) is a common and important pregnancy disorder with high blood pressure, proteinuria, and multi-organ vascular damage as its main characteristics, causing over 40,000 maternal deaths each year. Recent research suggests that PE can be divided into early onset and late onset subtypes, with different characteristics and outcomes. This study aims to explore the differences between the two subtypes and investigate the molecular expression differences in their placenta. The results showed that EOPE has significantly stronger homogeneity than LOPE and is characterized by hypoxia and HIF1A activation. The upregulation of glycolysis-related genes in EOPE, particularly the HK2 gene, was verified in independent validation data and single-cell data. Unsupervised clustering analysis suggests that LOPE may have at least two subtypes with different features. These findings support the hypothesis of subtyping PE based on gestational week and suggest that EOPE and LOPE should be studied as independent diseases.